IMPLEMENTATION OF INHERITANCE LAW IN THE COMMUNITY OF METRO CITY, LAMPUNG - Siradjuddin, Azmi (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
This study is aimed to understand and analyze the imp lementation of the Islamic law of inheritance in four eth nic groups, namely Lampungnese, Javanese, Padangnese and Sundanese, in Metro City, Lampung. It examined the implementation of the Islamic law of inheritance by these four eth nic groups concerning the understanding of the division of inheritance upon death. This is an empirical study using primary data obtained from interviewing 300 respondents and 30 informants, consisting of 10 judges, 5 heads of villages, 5 kiai/ Islamic leaders, and 10 Islamic/village figures. The secondary dat a were divided into three parts: primary legal materials, sec ondary legal materials, and tertiary legal materials. The data analysis was carried out in stages: collection, inventory, classification, construction, and descriptive analysis based on content analysis. The study found that the majority of people--those who are lacking religious understanding with various bac kgrounds-- carried out inheritance based on customary inheritance law. While those who have better understandings of religion --which is a minority-- carried out inheritance based on The Islamic inheritance law. This study also found that 93% of the people agreed that the Islamic inheritance law should be applied to inheritance law for Indonesian Muslim communities in the form of legislation products.